Community-Based Digital Support for Adolescent Violence Prevention and Emotional Well-Being - Prima Dewi Kusumawati; Reni Nurhidayah; Dhita Kurnia Sari; Koesnadi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2026)
Adolescent violence and emotional problems have become important public health concerns, while existing support services remain limited, fragmented, and often inaccessible for adolescents. This study aimed to evaluate the effectiveness of community-based digital support through the SPEAKUP! platform in improving violence prevention awareness and emotional well-being among adolescents. A randomized controlled trial was conducted among 416 adolescents from senior high schools and vocational schools in Pare District, Kediri Regency, Indonesia. Participants were randomly assigned into intervention and control groups. The intervention group received access to the SPEAKUP! platform for four weeks, including educational videos, self-screening, positive discussion forums, emotion journaling, and relaxation guidance, while the control group received conventional health education. Data were collected using validated questionnaires measuring violence prevention knowledge, attitudes, and emotional well-being before and after the intervention. The findings showed significant improvements in violence prevention knowledge and attitudes among adolescents in the intervention group compared with the control group. Emotional well-being also improved significantly, indicated by reduced emotional and behavioral difficulty scores after the intervention. The results suggest that community-based digital support provides adolescents with accessible, private, and engaging psychosocial support while strengthening preventive behaviors related to violence. Integrating digital support platforms into adolescent community health programs may enhance violence prevention and emotional support services in schools and community settings.